One repeated transplantation of allogeneic umbilical cord mesenchymal stromal cells in type 1 diabetes: an open parallel controlled clinical study - Lu, Jing; Shen, Shan-mei; Ling, Qing; Wang, Bin; Li, Li-rong; Zhang, Wei; Qu, Duo-duo; Bi, Yan; Zhu, Da-long (Stem cell research & therapy, 2021)
The preservation or restoration of β cell function in type 1 diabetes (T1D) remains as an attractive and challengeable therapeutic target. Mesenchymal stromal cells (MSCs) are multipotent cells with high capacity of immunoregulation, which emerged as a promising cell-based therapy for many immune disorders. The objective of this study was to examine the efficacy and safety of one repeated transplantation of allogeneic MSCs in individuals with T1D. This was a nonrandomized, open-label, parallel-armed prospective study. MSCs were isolated from umbilical cord (UC) of healthy donors. Fifty-three participants including 33 adult-onset (≥ 18 years) and 20 juvenile-onset T1D were enrolled. Twenty-seven subjects (MSC-treated group) received an initial systemic infusion of allogeneic UC-MSCs, followed by a repeat course at 3 months, whereas the control group (n = 26) only received standard care based on intensive insulin therapy. Data at 1-year follow-up was reported in this study. The primary endpoint was clinical remission defined as a 10% increase from baseline in the level of fasting and/or postprandial C-peptide. The secondary endpoints included side effects, serum levels of HbA1c, changes in fasting and postprandial C-peptide, and daily insulin doses. After 1-year follow-up, 40.7% subjects in MSC-treated group achieved the primary endpoint, significantly higher than that in the control arm. Three subjects in MSC-treated group, in contrast to none in control group, achieved insulin independence and maintained insulin free for 3 to 12 months. Among the adult-onset T1D, the percent change of postprandial C-peptide was significantly increased in MSC-treated group than in the control group. However, changes in fasting or postprandial C-peptide were not significantly different between groups among the juvenile-onset T1D. Multivariable logistic regression assay indicated that lower fasting C-peptide and higher dose of UC-MSC correlated with achievement of clinical remission after transplantation. No severe side effects were observed. One repeated intravenous dose of allogeneic UC-MSCs is safe in people with recent-onset T1D and may result in better islet β cell preservation during the first year after diagnosis compared to standard treatment alone. ChiCTR2100045434 . Registered on April 15, 2021-retrospectively registered, http://www.chictr.org.cn/.